A Novel Tightly Regulated Gene Expression System for the Human Intestinal Symbiont Bacteroides thetaiotaomicron - Horn, Nikki; Carvalho, Ana L.; Overweg, Karin; Wegmann, Udo; Carding, Simon R.; Stentz, Régis (Frontiers in Microbiology, 2016)
There is considerable interest in studying the function of Bacteroides species resident in the human gastrointestinal (GI)-tract and the contribution they make to host health. Reverse genetics and protein expression techniques, such as those developed for well-characterised Escherichia coli cannot be applied to Bacteroides species as they and other members of the Bacteriodetes phylum have unique promoter structures. The availability of useful Bacteroides-specific genetic tools is therefore limited. Here we describe the development of an effective mannan-controlled gene expression system for Bacteroides thetaiotaomicron containing the mannan-inducible promoter–region of an α-1,2-mannosidase gene (BT_3784), a ribosomal binding site designed to modulate expression, a multiple cloning site to facilitate the cloning of genes of interest, and a transcriptional terminator. Using the Lactobacillus pepI as a reporter gene, mannan induction resulted in an increase of reporter activity in a time- and concentration-dependent manner with a wide range of activity. The endogenous BtcepA cephalosporinase gene was used to demonstrate the suitability of this novel expression system, enabling the isolation of a His-tagged version of BtCepA. We have also shown with experiments performed in mice that the system can be induced in vivo in the presence of an exogenous source of mannan. By enabling the controlled expression of endogenous and exogenous genes in B. thetaiotaomicron this novel inducer-dependent expression system will aid in defining the physiological role of individual genes and the functional analyses of their products.